Secure Transmission of Data Using DNA Technology (International Journal of Engineering and Computer Science, 2018)
The traditional encryption techniques use mathematical and theoretical concepts. With the advances in technology, the intruders are able to decrypt the private data and steal the secretive information easily. Thus cryptography using DNA technology can be viewed as a new hope for unbreakable algorithms. The text data is encrypted using DNA technology. A key is generated and encrypted. The encrypted text and key are then hidden in an image by applying Discrete Cosine Transform (DCT) or Discrete Wavelet Transform (DWT) to generate a DCT watermarked image or a DWT watermarked image. The watermarked image is transmitted to the receiver. Encryption followed by steganography further enhances the security of the data being transmitted. The proposed algorithm is evaluated using correlation coefficient, PSNR, MSE and embedding capacity